Pengaruh Pertumbuhan Perusahaan dan Intensitas Modal Terhadap Konservatisme Akuntansi dengan Managerial Ownership sebagai Variabel Moderasi - Wijaya, Christina; Tjakrawala, Kurniawan (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to determine the effect of company growth and capital intensity on accounting conservatism with managerial ownership as moderating variable through annual financial reports of manufacturing companies listed on IDX. The population in this study was obtained using purposive sampling method on listed manufacturing companies on IDX with criterias that had been selected, including manufacturing companies that have financial statement from 2015 until 2019. Based on the research method, the samples obtained were 200 manufacturing companies. The analytical method is double linear regression with SPSS version 23 and Microsoft Excel. This study proves that company growth has a significant effect on accounting conservatism, capital intensity has a significant effect on accounting conservatism, managerial ownership moderates the effect of company growth on accounting conservatism, managerial ownership moderates the effect of capital intensity on accounting conservatism.